Mannose-Binding Lectin Binds to Amyloid β Protein and Modulates Inflammation. (26th March 2012) - Larvie, Mykol; Shoup, Timothy; Chang, Wei-Chuan; Chigweshe, Lorencia; Hartshorn, Kevan; White, Mitchell R.; Stahl, Gregory L.; Elmaleh, David R.; Takahashi, Kazue
Abstract : Mannose-binding lectin (MBL), a soluble factor of the innate immune system, is a pattern recognition molecule with a number of known ligands, including viruses, bacteria, and molecules from abnormal self tissues. In addition to its role in immunity, MBL also functions in the maintenance of tissue homeostasis. We present evidence here that MBL binds to amyloid β peptides. MBL binding to other known carbohydrate ligands is calcium-dependent and has been attributed to the carbohydrate-recognition domain, a common feature of other C-type lectins. In contrast, we find that the features of MBL binding to A β are more similar to the reported binding characteristics of the cysteine-rich domain of the unrelated mannose receptor and therefore may involve the MBL cysteine-rich domain. Differences in MBL ligand binding may contribute to modulation of inflammatory response and may correlate with the function of MBL in processes such as coagulation and tissue homeostasis.